A functional anionic metal–organic framework for selective adsorption and separation of organic dyes. (15th March 2019) - Cui, Ying-Ying; Zhang, Juan; Ren, Ling-Ling; Cheng, Ai-Ling; Gao, En-Qing
Graphical abstract: A 3D anionic MOF (Zn-1) containing large 3D intersecting channels modified with functional groups has been synthesized and the selective adsorption of organic dyes has been systematically investigated. Abstract: A 3D porous anionic MOF, [(CH3 )2 NH2 ][Zn6 (μ3 -OH)(μ4 -O)(NSBPDC)5 (H2 O)2 ]·DMF·12H2 O n (Zn-1 ) (H2 NSBPDC = 6-nitro-2, 2′-sulfone-4, 4′-dicarboxylic acid), has been synthesized and characterized.Zn-1 exhibits a rare 5-connected 'sqp' net and contains large 3D intersecting channels modified with functional groups. Notably, Zn-1 can adsorb cationic dyes selectively and effectively, even for large molecules including Rhodamine B and Crystal Violet. The influences of the constant time and initial concentration of MB on the adsorption capacity ofZn-1 have been studied in detail. Furthermore, the kinetic research indicates that the adsorption of MB matches well with the pseudo second-order model. In addition, the material ofZn-1 is reusable, and the adsorbed dye (MB) can be released in saturated DMF/ethanol solution of LiNO3 .